The Evolution of the Middle Class in Latin America - Tornarolli, Leopoldo (2014)
Latin American countries have always been characterised by relatively high levels of income inequality, even taking into accounttheir degree of economic development. If such ‘excess inequality’ is combined with the fact that these are mostly middle-incomeand low-income countries, it can be understood that, in general, the middle class has not historically represented a significantproportion of the population in many countries in the region.